Potential impact and phenology of the biological control agent, Hypena opulenta on Vincetoxicum nigrum in Michigan. Issue 6 (3rd June 2022) - Alred, Brianna; Hufbauer, Ruth A.; Szűcs, Marianna
ABSTRACT: Pre-release studies indicate that the defoliating moth, Hypena opulenta, can be effective at reducing biomass, survival, and seed production of invasive swallow-wort vines. However, laboratory studies to date report higher defoliation rates and larval densities than are present in the field five years post-release in Canada. To understand the consequences of H. opulenta feeding on black swallow-wort, Vincetoxicum nigrum, at more realistic densities, we conducted experimental cage releases in Michigan. We also evaluated the phenology of the moth. We released 1, 2, or 5 pairs of H. opulenta on caged swallow-wort and measured resulting larval densities, defoliation levels, plant fecundity and survival for two years. To determine which release date may result in two generations of H. opulenta in Michigan, we released adults in June or July at one sunny and one shaded location and followed their phenology. Larval densities and damage increased with release size, but plant survival and fecundity were not affected. Hypena opulenta produced two generations when released in June at >15 h day length. Survival of H. opulenta and defoliation rates were higher in the shaded environment. These results support previous findings regarding better performance of H. opulenta at shaded sites, however, larval densities achieved in the field both in this experiment and at Canadian release sites are still too low to negatively affect swallow-wort fitness. Moreover, we were unable to confirm overwintering success and thus establishment of H. opulenta in Michigan is not yet known.